Development and validation of the academic stress inventory - Sari, Rosita Purnama; Faradina, Nabila Huda; Ramadhan, Nafylays Nurlaely Kusuma; Rahman, Diniy Hidayatur; Affandi, Achmad Jazuli (Proceedings Series of Educational Studies, 2024)
This study aimed to develop and validate an Academic Stress Inventory for high school students at SMAN 1 Probolinggo. Utilizing a modified Borg & Gall Research and Development (R&D) model, the inventory was based on Gadzella & Masten's (2005) framework, encompassing academic stressors and reactions. Initially comprising 52 items, it was pilot-tested with 203 tenth-grade students using a cross-sectional design. The sample size was obtained using simple random sampling to ensure a representative sample of the student population. Validity was assessed using Pearson Correlation, resulting in 51 validated items. The inventory showed high reliability with a Cronbach's Alpha of 0.934. It categorizes academic stress into low, moderate, and high levels. The data collection procedure involved administering the inventory during school hours. This validated tool addresses a critical gap at SMAN 1 Probolinggo, providing a structured measure of academic stress. Its application promises to enhance stress management programs, fostering a supportive academic environment and promoting student well-being and success Keywords: academic stress; inventory; senior high school students